Solve employee problems before they start : resolving conflict in the real world - Warrick, Scott (Society for Human Resource Management, 2019)
With compassion, clarity, and conviction (and a dash of comedy for good measure) popular speaker and employment law attorney Scott Warrick distills conflict resolution to just three simple moves: Empathic Listening, Parroting, and Rewards (EPR). --